Desenvolvimento de um software para preparação de aulas de inglês com corpora - Moreira Filho, José Lopes (2007)
The main aim of this study is the development of semi-automatic software to prepare reading materials for English as a Second Language classes, using corpora to elaborate teaching material that explores real language. The theoretical underpinning of the research is provided by Corpus Linguistics; a study area in the domain of Applied Linguistics that takes an empirical approach to language and sees it as a probabilistic system. It is based on the analysis of large amounts of real linguistic data by means of computers (Berber Sardinha, 2004). More specifically, the corpus based research area concerned with the teaching process and foreign language learning informs this study. Some references can be found in Berber Sardinha (2004), Hunston (2002), Kennedy (1998), Johns (1991), Sinclair (1991), Flowerdew (1993), Fox (1998), Trible & Jones (1990). In addition to Corpus Linguistics, thisinvestigation is also based on previous studies in the Teaching of Reading, such as those from (Grellet, 1981; Nuttal, 1988; Scott et al., 1984) for creating a standard activity model to develop a semi-automatic tool to prepare English reading lessons in Visual Basic 6 (VB6). Our intention is to make an original contribution to English Language Teaching at the High School level in public schools. The goals are twofold: to develop innovative studies in this particular subject and to provide an opportunity for the use of authentic texts and corpora in didactic activities. Although literature in the area is extensive, there still seems to be a need for research on the development of computational tools that will make it possible to use the same resources used in corpora exploration for language teaching in Brazilian public schools. Two corpora were used in the study: a reference corpus and a training corpus. The reference corpus was the British National Corpus (BNC), released in 1995 with more than 100,000,000 words. The training corpus, whose goal is to test the software functions, was collected from the Internet and has a total of 80 texts from varied genre